(NgEOHIMIQ PRIRODNYH WOD (B:s (NtRUDY wTOROGO MEVDUNARODNOGO SIMPOZIUMA(B, (NrOSTOW(B-(NNA(B-(NdONU(B, 17-22 (NMAQ (B1982 (NG(B. /s - (NnIKANOROW(B, (Na(B.(Nm(B.s; (NwALQ[KO(B, (Nm(B.(Ng(B.s; (NrOSTOWSKIJ GIDROHIMI^ESKIJ INSTITUTs; (NmEVDUNARODNYJ SIMPOZIUM (B"(NgEOHIMIQ PRIRODNYH WOD(B"s 17-22 (NMAQ (B1982 :s (NrOSTOW NA dONU(B)s ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1985)
(NrEZ(B. (NST(B.: (NANGL(B.s
Keywords: (NgIDROHIMIQs